THE DEVELOPMENT OF INQUIRIES LEARNING MODEL WITH A CONTEXTUAL APPROACH - Muh Bukhari (Scientia Integritas Utama, 2022)
This study aims to produce an inquiry learning model with a contextual approach to social studies learning, which is realized into three product forms: teacher books, student books, and model books. Field trials in this study consisted of 20 students, eight male students and twelve female students. This research uses a developmental research model. This development research uses the Borg and Gall development model, which is carried out in five stages: the needs analysis stage, the design stage, the prototyping stage, the field trial stage, and the product revision stage. The results of this study indicate that: (1) Based on the validator's assessment, the products developed in the form of teacher books, student books, and model books are included in the